Herculine : a novel - Byron, Grace (Saga Press, 2025)
"Herculine's narrator has demons. Sure, her life includes several hallmarks of the typical trans girl sob story-conversion therapy, a string of shitty low-paying jobs, and even shittier exes-but she also regularly debates sleep paralysis demons that turn to mist soon after she wakes and carries vials of holy oil in her purse. Nothing, though, prepares her for the new malevolent force stalking her through the streets of New York City, more powerful than any she's ever encountered. Desperate to escape this ancient evil, she flees to rural Indiana, where her ex-girlfriend started an all-trans girl commune in the middle of the woods. The secluded camp, named after 19th-century intersex memoirist Herculine Barbin, is a scrappy operation, but the shared sense of community among the girls is a welcome balm to the narrator's growing isolation and paranoia. Still, something isn't quite right at Herculine. Girls stop talking as soon as she enters the room, everyone seems to share a common secret, and the books lining the walls of the library harbor strange cryptograms. Soon what once looked like an escape becomes a trap all its own.."--Provided by publisher.